Lithium Niobate Single Crystals and Powders Reviewed—Part II - Farias, Rurik (2020)
A review on lithium niobate single crystals and polycrystals has been prepared. Both the classical and recent literature on this topic is revisited. It is composed of two parts with several sections. The current part discusses the available defect models (intrinsic), the trends found in ion-doped crystals and polycrystals (extrinsic defects), the fundamentals on dilute magnetic oxides, and their connection to ferromagnetic behavior in lithium niobate.